Konflik Tokoh Utama Dalam Novel Peterpan Karya J.M Barrie - Ellya Wulandari (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This study aims to analyze the forms of internal and external conflicts experienced by the main characters in the novel Peter Pan by J.M. Barrie and how these conflicts affect the development of the storyline. This research uses a qualitative descriptive method with an objective approach, which emphasizes the analysis of intrinsic elements such as characters, conflicts, and plots. Data were collected through reading and recording techniques against novel texts, then analyzed with the classification of conflicts and their role in narrative structure. The results of the study show that the main character, Peter Pan, experiences internal conflicts in the form of fear of adulthood, emotional dilemmas, and identity crises, as well as external conflicts involving other characters such as Captain Hook, Wendy, and Tinker Bell. These conflicts prove to be the main drivers of the storyline, influencing character development, and reinforcing the novel's philosophical message about the conflict between childhood freedom and the responsibilities of adulthood. This research enriches the understanding of character dynamics in fiction and shows the importance of conflict as a structural and thematic element in literary works.